LongTerm Outcomes of Three-Port Laparoscopic Right Hemicolectomy Versus Five-Port Laparoscopic Right Hemicolectomy: A Retrospective Study - Zhang, Tao; Zhang, Yaqi; Shen, Xiaonan; Shi, Yi; Ji, Xiaopin; Wang, Shaodong; Song, Zijia; Jing, Xiaoqian; Ye, Feng; Zhao, Ren (Frontiers in Oncology, 2021)
Purpose: The aim of this study is to compare the long-term outcomes of TPLRC (Three- port laparoscopic right hemicolectomy) and FPLRC (Five-port laparoscopic right hemicolectomy) with retrospective analysis. Methods: 182 patients who accepted laparoscopic right hemicolectomy with either three ports (86 patients) or five ports (96 patients) from January 2012 to Jun 2017 were non-randomly selected and analyzed retrospectively. Results: More lymph nodes were harvested in the TPLRC group than in the FPLRC group (17.5 (7), 14 (8) ml, p<0.001). Less blood loss in the TPLRC group (50 (80) vs 100 (125) ml, p=0.015). No significant differences in the other short-term or oncological outcomes between the two groups. Overall survival and disease-free survival were equivalent. Conclusions: TPLRC is recommendable as it guarantees short and long-term equivalent outcomes compared with FPLRC.